Being Convinced and Taking Responsibility: A Qualitative Study of Family Members' Experience of Organ Donation Decision and Bereavement After Brain Death*. Issue 4 (April 2019) - Kentish-Barnes, Nancy; Cohen-Solal, Zoé; Souppart, Virginie; Cheisson, Gaëlle; Joseph, Liliane; Martin-Lefèvre, Laurent; Si Larbi, Anne Gaelle; Viquesnel, Gérald; Marqué, Sophie; Donati, Stéphane; Charpentier, Julien; Pichon, Nicolas; et al.
Abstract : Objectives: Family members of brain dead patients experience an unprecedented situation in which not only they are told that their loved one is dead but are also asked to consider organ donation. The objective of this qualitative study was to determine 1) what it means for family members to make the decision and to take responsibility, 2) how they interact with the deceased patient in the ICU, 3) how family members describe the impact of the process and of the decision on their bereavement process. Design: Qualitative study using interviews with bereaved family members who were approached for organ donation after the death of their relative in the ICU (brain death). Setting: Family members from 13 ICUs in France. Subjects: Bereaved family members who were approached for organ donation after the death of their relative in the ICU (brain death). Intervention: None. Measurements and Results: Twenty-four interviews were conducted with 16 relatives of organ donor patients and with eight relatives of nonorgan donor patients. Three themes emerged: 1) taking responsibility—relatives explain how they endorse decisional responsibility but do not experience it as a burden, on the contrary; 2) ambiguous perceptions of death—two groups of relatives emerge: those for whom ambiguity hinders their acceptance of the patient's death; those for whom ambiguity is an opportunity to accept the death and say goodbye; and 3) donation as a comfort during bereavement. Conclusions: In spite of caregivers' efforts to focus organ donation discussions and decision on the patient, family members feel a strong decisional responsibility that is not experienced as a burden but a proof of their strong connection to the patient. Brain death however creates ambivalent experiences that some family members endure whereas others use as an opportunity to perform separation rituals. Last, organ donation can be experienced as a form of comfort during bereavement provided family members remain convinced their decision was right. Abstract : Supplemental Digital Content is available in the text.